Inhibition of recall responses through complementary therapies targeting CD8(+) T cell- and alloantibody-dependent allocytotoxicity in sensitized transplant recipients - Zimmerer, Jason M. (2012)
Allospecific T memory cell responses in transplant recipients arise from environmental exposure to previous transplantation or cross-reactive heterologous immunity. Unfortunately, these memory responses pose a significant barrier to the survival of transplanted tissue. We have previously reported that concurrent inhibition of CD154 and LFA-1 suppresses primary CD8-dependent rejection responses that are not controlled by conventional immunosuppressive strategies. We hypothesized that CD154- and LFA-1-mediated inhibition, by targeting activation as well as effector functions, may also be efficacious for the control of alloreactive CD8(+) T cell responses in sensitized hosts. We found that treatment with anti-LFA-1 mAb alone enhanced transplant survival and reduced CD8-mediated cytotoxicity in sensitized CD4 KO recipients. However, treatment with anti-CD154 mAb alone did not have an effect. Notably, when both CD4- and CD8-dependent rejection pathways are operative (wild-type sensitized recipients), LFA-1 significantly inhibited CD8-mediated in vivo allocytotoxicity but did not correspond with enhanced hepatocyte survival. We hypothesized that this was due to alloantibody-mediated rejection. When anti-LFA-1 mAb treatment was combined with macrophage-depletion, which we have previously reported impairs alloantibody-mediated parenchymal cell damage, in vivo cytotoxic effector function was significantly decreased and was accompanied by significant enhancement of hepatocyte survival in sensitized wild-type recipients. Therefore, LFA-1 is a potent therapeutic target for reduction of CD8-mediated cytotoxicity in sensitized transplant recipients and can be combined with other treatments which target non-CD8-mediated recall alloimmunity.